The effect of jumping rope and calf raise exercises on students' leg muscle strength - I Gede Komang Widi Nugraha; I Made Satyawan; I Komang Sukarata Adnyana (Physical Education Departement of University PGRI Jombang, 2025)
This study aims to analyze the effect of Jumping-rope and Calf-rise training on increasing leg muscle strength. The type of research is a quasi-experiment with the non-randomized pretest posttest control group design. The research subjects were 30 people. Leg muscle strength was measured using the Leg dynamometer test and the data were analyzed using a one-way ANOVA test, followed by the least significant difference (LSD) test at a significance level (a) of 0.05 with the help of the SPSS 16.0 computer program. Description of research data from the variable leg muscle strength in the Calf-Rise group which increased by 3.70, the Jumping-Rope group experienced an increase of 5.80, and the control group experienced an increase of 2.40. The results of data analysis using the one-way ANOVA test showed that Jumping-Rope and Calf-Rise training had an effect on increasing leg muscle strength with a significance value of 0.000 (sig <0.05) and there were differences in the influence of each group. Based on the least significant difference (LSD) test, it was found that the Jumping-Rope training mean difference was 2.10000, which was better than the Calf-Rise training mean difference of -2.10000. The results of this research can be concluded that: (1) Jumping-Rope and Calf-Rise research has an effect on increasing leg muscle strength, (2) There is a difference in the influence between Jumping-Rope and Calf-Rise training which has an effect on increasing leg muscle explosive power, where training Jumping-Rope has a better effect than Calf-Rise training in increasing leg muscle strength. For sports players, it is recommended that they use Jumping-Rope and Calf-Rise training as a way to increase Leg Muscle strength